Vancomycin-Associated Acute Kidney Injury in a Large Veteran Population - Gyamlani, Geeta (Am J Nephrol, 2019)
BACKGROUND: To determine the association of vancomycin with AKI in relation to its serum concentration value, and to examine the risk of AKI in patients treated with vancomycin when compared with a matched cohort of patients receiving non-glycopeptide antibiotics (linezolid/daptomycin). METHODS: From a cohort of >3 million US veterans with baseline eGFR ≥60ml/min/1.73m(2), we identified 33,527 patients who received either intravenous vancomycin (N=22,057) or non-glycopeptide antibiotics (linezolid/daptomycin, N=11,470). We examined the association of the serum trough vancomycin level recorded within the first 48 hours of administration with subsequent AKI in all patients treated with vancomycin, and association of vancomycin vs. non-glycopeptide antibiotics use with the risk of incident AKI. RESULTS: The overall multivariable adjusted ORs of AKI stages 1, 2 and 3 in patients on vancomycin vs. non-glycopeptides were 1.1 (1.1–1.2), 1.2 (1–1.4) and 1.4 (1.1–1.7), respectively. When examined in strata divided by vancomycin trough level, the odds of AKI were similar or lower in patients receiving vancomycin compared to non-glycopeptide antibiotics as long as serum vancomycin levels were ≤20 mg/L. However, in patients with serum vancomycin levels >20 mg/L, the ORs of AKI stages 1, 2 and 3 in patients on vancomycin vs. non-glycopeptide antibiotics were 1.5 (1.4–1.7), 1.9 (1.5–2.3) and 2.7 (2–3.5), respectively. CONCLUSIONS: Vancomycin use is associated with a higher risk of AKI when serum levels exceed >20 mg/L.